Hubungan Kadar Feritin Serum dengan Kadar Enzim SGOT dan SGPT pada Pasien Thalasemia β Mayor - Rita Agustina; Zulhafis Mandala; Ressy Nirmala Indah (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Thalassemia is a genetic blood disorder that can cause hemolysis in hemoglobin. So the patient must get a transfusion for life. The transfusion is done continuously, this is what causes patients with thalassemia β major to have iron buildup in their body. So the levels of Ferritin, SGOT, and SGPT enzymes can be increased in patients with β major thalassemia. This study aims to determine the relationship between serum ferritin with SGOT and SGPT enzymes in thalassemia β major patients. This research uses an analytic method with a cross-sectional approach. The subjects in this study were 60 samples. The instrument used was the patient's medical record data. Statistical analysis using the Chi-Square test showed a p-value 0.005 (p-value <0.05) for serum ferritin with SGOT. And for serum ferritin with SGPT enzymes, p-value 0.004 (p-value <0.05), it means that there is a relationship between serum ferritin and SGOT and SGPT enzymes. There is a correlation between serum ferritin with SGOT and SGPT enzymes in β major thalassemia patients at Abdul Moeloek Hospital Bandar Lampung.